Deterioro cognitivo y adherencia al tratamiento en pacientes con diabetes mellitus tipo 2 del centro de salud Zamora Huayco - Chamba León, Josué Marcelo (2023)
Mellitus diabetes type 2 is a chronic-metabolic disease prevailing in the population, causing acute and chronic complications in patients with inadequate therapeutic adherence; One of this kind is the appearance of cognitive deterioration at an earlier age than the non-diabetic population. The purpose of this study was to determine the presence and degrees of cognitive impairment in patients aged between 50 and 64, who have been treated at the "Zamora Huayco" Health Center and the level of adherence to treatment during the period March 2021-April 2022. It is a quantitative, cross-sectional study; developed in a population of 42 patients. Obtaining degrees of cognitive impairment according to the Mini-Mental cognitive test; Possible cognitive impairment 14.3% (n=6), mild cognitive impairment 4.76% (n=2). Adherence to treatment in the population according to the EADTM-III test ranged from a high level of adherence in 59.52% (n=25) to medium-low in 40.47% (n=17). The female population of the aged group between 60 and 64, presents the highest number of cases of impairment in the cognitive sphere 14.28% (n=6), with the male gender being the group with the lowest number of cases at 4.76% ( n=2). It can be concluded that cognitive impairment in Type 2 Diabetes Mellitus presents a statistically significant relationship with the level of adherence to treatment, which is more prevalent at medium-low levels and observed mostly in the female gender at older ages